IMPLEMENTASI PROGRAM KLINIK MAPEL DALAM MENINGKATKAN HASIL BELAJAR - Yusdarina Yusdarina; Napsawati Napsawati; Reski Idamayanti (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to describe the implementation of clinical courses in improving learning outcomes at SMA IT Shohwatul Is'ad. simple statistical calculations. Data collection techniques through observation, interviews and documentation. The results of the study indicate that the implementation of the subject clinical program in physics learning begins with the process of analyzing the items of the Mid-Semester Assessment in which the results of the analysis are used as a reference for implementing the subject clinic. In addition, the implementation of the maple clinic is carried out on a scheduled basis following the schedule determined by the school outside of effective learning hours and the procedure when the maple clinic takes place is completely left to the subject teacher in which the teacher applies fun methods and strategies so that students learn optimally. The results of the evaluation after the implementation of the clinical mapel showed an increase in student learning outcomes.